POTENSI ZEOLIT ALAM DAN CaO DARI CANGKANG TELUR AYAM SEBAGAI KATALIS DALAM PEMBUATAN BIODIESEL DARI TREATED WASTE COOKING OIL - Taslim, Meilia, Nike Taruna (Universitas Sumatera Utara, 2016)
Biodiesel is an alternative fuel for diesel engines which is produced from either vegetable oils or animal fats. Treated Waste Cooking Oil (TWCO) was the pretreated WCO using activated carbon to reduce the high content of free fatty acid (FFA). The objective of this study was to discover the potential of catalyst which was the mixture of natural zeolite and CaO derived from the chicken eggshells in producing biodiesel with TWCO as feedstock. Chicken eggshells were calcined at the temperature of 1000 oC for 2 hours. Effect of using the catalyst, natural zeolite and CaO, was investigated in this study. The properties of biodiesel such as methyl ester content, density, kinematic viscosity and flash point were evaluated and compared to the Indonesian Standard (SNI). In this study, the biodiesel yield for catalyst of natural zeolite, CaO, and mixture of both were 7,28%; 51,17%; and 87,40% respectively. The biodiesel produced in this study was comparable to the SNI standard and that the addition of natural zeolite could enhance the catalytic activity. Therefore, it is highly potential as low-cost catalyst in producing biodiesel.